The Costs of Crime in Argentina - Shehadi, Agustin (2018)
The main goal for this paper is to deal with the challenging task of estimating the direct and indirect costs of crime and violence for Argentina as a decomposition by jurisdiction (23 provinces). With Costs of Crime we are referring not only to material losses or damages but also to ’’everything that means a welfare loss for society derived for crime”. This exercise has the difficulty of assigning a monetary value to aspects such as human life or the productivity loss suffered by a person in jail. In this study we categorize the welfare costs of crime in three main categories: Private Costs, Governmental Costs and Social Costs. There is a great discussion related to the methodology that this task implies, the so-called Hedonic Prices (Bishop and Timmis -2011, Gaviria et al - 2008), Contingent Valuation (Zarakin, Cates and Bala -2005, Cohen et al -2004, Ronconi -2009), and The Accounting of Losses and Expenses (Cohen -2005, Brand and Price -2000, Rollings -2008). The method adopted in this paper is the latter; we opted this way of analysis because this method also includes the identification of intangible costs, such as the weakening of the community’s social capital and the social opportunity cost of somebody dedicated to crime instead of lawful activities, and the advantage of a clear distinction of the sources of the welfare loss of crime in the society.